Analisis Kekuatan Pukulan Atlet Beladiri Menggunakan Metode Pengukuran Matematis dan Alat Ukur Berbasis Mikrokontroller: Analisis Kekuatan Pukulan Atlet Beladiri Menggunakan Metode Pengukuran Matematis dan Alat Ukur Berbasis Mikrokontroller - Ratna Mustika Yasi; Mohammad Nurcholis (Prodi Teknik Elektro Universitas PGRI Banyuwangi, 2019)
The research aims to compare the value of the strike strength of martial arts athletes mathematically and by using measuring instruments. This measuring tool is used to measure the strength of a martial arts athlete that is read by the system. This research was conducted in several steps, namely: literature study, tool testing, results, analysis and discussion, and conclusions. The measuring instrument of the athlete's stroke strength was carried out by a prototype performance test by 8 martial arts athletes with 5 strokes using a front or straight punch with a predetermined target distance. Furthermore, the data will be tabulated and calculated based on a predetermined formula. Based on the results of the study, it can be concluded that the ADC data with the calculated data mathematically have physical similarities. So based on the analysis of the sensors used to capture the incoming pressure on the microcontroller has a patterned value that is the same as the mathematical calculation data. Where the stroke power is calculated mathematically influenced by the mass of the fist, kinetic energy, target distance, time, and force. Whereas the work method of measuring the strength of a martial arts athlete, the FSR sensor receives the incoming pressure in the form of a blow, then the data is sent to the ATmega328 microcotroller for processing, then the data is sent to the seven segment to bring up the incoming pressure value in the form of numbers.